Innovativeness of family businesses in Slovenia: Do heirs follow the founders? - Marina Letonja; Marjana Merkač; Ivana Vrdoljak (Business Systems Research (BSR), 2021)
Background: The innovativeness of founders and their heirs and family businesses (FBs) is a relatively unexplored field of research, and its understanding is incomplete and inconsistent. Objectives: The goal is to compare the founders' innovativeness and investigate the relationship of life-long learning with the innovativeness of heirs in FBs. Methods/Approach: The paper is based on research, including a survey on FBs in Slovenia. The differences in the innovativeness of the two groups - founders and heirs are compared, and the strength of the dependence of the life-long learning and innovativeness through the external training of heirs determined. Results: The innovativeness of founders and heirs in FBs, measured by the number of new product and service lines and by the number of new processes that founders and heirs in FBs have developed or started marketing in the last five years, shows higher results for the founders. Life-long learning through external training correlates positively with the innovativeness of heirs. Conclusions: An appropriate culture for innovation needs to be created in FBs to foster innovativeness among heirs, which can be supported by life-long learning.
Keywords: L26; O31; 330; family business; entrepreneurship; innovativeness; life-long learning